Tumor Interstitial Fluid and Gastric Cancer Metastasis： An Experimental Study to Verify the Hypothesis of ＂Tumor-Phlegm Microenvironment - 陈大志 矫健鹏 巨大维 叶敏 张璇 徐晶钰 陆烨 何金 魏品康 杨明会 (Chinese journal of integrative medicine, 2012)
Objective： To extract tumor interstitial fluid （TIF） from MKN-45 gastric cancer which is similar to ＂muddy phlegm＂ in Chinese medicine and observe influences of MKN-45 tumor interstitial fluid （MKN-45 TIF） intervention on metastasis of gastric cancer and on the expressions of vascular endothelial growth factor （VEGF）, kinase insert domain containing receptor （KDR）, epithelial-cadherin （E-cad）, cyclooxygenase-2 （COX-2）, intercellular adhesion molecule-1 （ICAM-1） and telomerase genes and proteins in primary tumor tissue. Methods： An MKN-45 tumor-bearing model was established in 50 nude mice. The modeled animals were equally randomized to 5 groups： the simple tumor-bearing group （model group）, the normal saline （NS） via tail vein injection （i.v.） group （NS i.v. group）, MKN-45 TIF i.v. group （TIF i.v. group）, NS intraperitoneal injection （i.p.） group （NS i.p. group）, and MKN-45 TIF i.p. group （TIF i.p. group）. The TIF and NS intervention groups received injection （i.p. or i.v.） of MKN-45 TIF or NS twice a week, 0.2 mL at a time. After 8 weeks, the primary tumors were removed, weighed and HE stained to observe tumor metastasis. The primary tumor tissues were analyzed by immunohistochemistry and real-time quantitative PCR to detect expressions of VEGF, KDR, E-cad, COX-2, ICAM-1, and telomerase genes and proteins in different groups. Results： There were significant differences in tumor weight between TIF intervention groups and the model and NS intervention groups. Tumor metastasis was observed in all 5 groups, but the tumor metastasis rate in TIF intervention groups was significantly higher than those in the model and NS intervention groups. The gene and protein expressions of gastric cancer-related factors VEGF, KDR, COX-2, ICAM-1 and telomerase were unregulated while the gene and protein expressions of E-cad were downregulated in TIF intervention groups. Conclusions： TIF promotes tumor growth, invasion and metastasis of gastric cancer. These findings provide preliminary experimental clues for verifying the hypothesis of ＂tumor-phlegm microenvironment＂.